A novel N100 and N170 wave degrading scale by using hybrid fuzzy logic control method for driving alertness measurement - Mohamed Aminuddin, Mai Mariam; Mustaffa, Izadora; Brahin, Noor Mohd Ariff (Universiti Teknikal Malaysia Melaka, 2019)
Previous studies have shown that degrading of N100 and N170 waves amplitudes are correlate with higher accident and broken rules in driving experiment. Hence, a foundation of developing a device to detect attention alertness during driving is promising. However, due to variability of the amplitude degrading value among subjects and some of them gives false positive results, the determination of the optimum thresholds to classify the degree of significant degrading of the N100 and N170 wave amplitude is impossible. In engineering application, the threshold value is important in order to give the correct measurement to activate the actuator. Hence, in this proposal, the aims are for a first time to formulate a scale of N100 and N170 amplitude degrading, to define a threshold to differentiate between significant degrading and not significant degrading of the response and to analyse the feasibility of the scale to be used to measure attention alertness while driving. This study proposes a state of the art hybrid analysis technique i.e., mean and fuzzy logic to classify degrading value into scale of very significant degrading, less significant degrading, no changes, less attention and very significant attention. The obtained scale helps to determine the threshold that could be used as foundation to design a device that alerts one vigilant on the road. With this device, hopefully the statistic of road accident will decrease. This scale also could be used in other evoked response potential amplitude degrading/habituation study or applications.